Мodern views on the pathogenetic and prognostic aspects of prolonged and postterm pregnancy. - Yashchenko, L. M. (Морфологія / Morphologia / Morfologìâ, 2018)
The etiology and pathogenesis of post-term pregnancy to date have not been studied sufficiently, despite the considerable arsenal of scientific publications devoted to this problem.Post-term pregnancy should be considered as a pathological problem, which depends on both the mother’s condition and the condition of the fetus. The scientific literature highlights a number of reasons for pregnancy overcoming: a change in the hormonal state (high levels of progestins and low estrogen), changes in myometrium, dysfunction of the pituitary-adrenal system of the fetus, changes in the central nervous system. With the onset of pregnancy, its course, development and the nature of generic activity are associated with corticosteroids, chorionic gonadotrophin, placental lactogen, oxytocin, catecholamines, acetylcholine, serotonin, histamine and prostaglandins, as well as psychological traumas, toxicosis of the second half of pregnancy. The role of metabolic processes such as acidosis, change of pH-cord blood, deficiency of vitamins D, C, B, P, E, as well as reduction of trace elements such as copper, zinc, magnesium in blood, myometrium and placenta are also shown. The role of the immune factor in the etiology of post-term pregnancy is shown. Changing the equilibrium in the ratio of transplacental immunity and immunological tolerance. When post-term pregnancy occurs in the blood of pregnant women, there are no T-killers against fetal cells, high T-supressor pregnancy products are preserved. One of the factors in post-term pregnancy is the reduction of nitric oxide secretion by the endothelium of the cervical vessels. The leading role belongs to neurohumoral factors of regulation of the state of the uterus. When post-term pregnancy is occurs declared and sclerotic processes in the vessels of the placenta and placental place, the thin of the hematochorial barrier, apoptosis placental cells, changes in the morphology of vessels of the umbilical cord, microcirculation disorders. As a result, the fetus is stretching the cavity of the right ventricle and changing the frequency of cardiac contractions, decreasing its motor activity. Ultrasound examination for pregnancy dates reduces the mistake of the diagnosis. Consequently, in the scientific literature, there are many conceptions of post-term pregnancy, each of which has the right to exist and all of them are important prognostic tests, therefore, a thorough examination of pregnant women is necessary taking into account all possible risk factors for post-term pregnancy.